Managing COVID-19 Pandemic in Teaching Hospitals: An Early Preparedness Setting (Pengurusan Pandemik COVID-19 di Hospital Pengajar: Suatu Penetapan Persediaan Awal) - NAW, ZMAWATI MOHAMMED; AIZUDDIN, AZIMATUN NOOR; HOD, ROZITA; AHMAD, NORFAZILAH; DAUD, FAIZ; SALLEH, SHARIFAH AZURA; KORI, NAJMA; PERIYASAMY, PETRICK; HASSAN, MOHD ROHAIZAT; HARUNARASHID, HANAFIAH; JUSOFF , KAMARUZAMAN; ARIFIN, MOHD AFIQ (Journal of Ecohumanism, 2024)
The World Health Organization (WHO) declared the 2019-20 coronavirus disease (COVID-19) outbreak a pandemic on 11th of March 2020. The Ministry of Health, Malaysia has made preparations for the involvement of all government hospitals, including some teaching hospitals. This report elaborates and discusses the early establishment of the Hospital Canselor Tuanku Muhriz Crisis Preparedness and Response Centre (HCTM CPRC), highlighting how teaching hospitals function in handling the clinical and epidemiological management of COVID-19 among hospital staff. The setting comprises of four critical functions of the HCTM CPRC, namely case investigation, close contact tracing, surveillance for data reporting and risk communication. This report highlighted that a CPRC in teaching hospitals benefits not only the patients and the hospital administration but also all hospital staff, especially in managing COVID-19 pandemic emergency crisis.